Electro-Oxidation Mechanism of Meloxicam and Electrochemical Sensing Platform Based on Graphene Nanoparticles for its Sensing Pharmaceutical Sample - Eroğlu, Mehmet E.; Bayraktepe, Dilek E.; Polat, Kamran; Yazan, Zehra (Current Pharmaceutical Analysis, 2019)
Background: Electrochemical oxidation mechanism and electrochemical determination of meloxicam (M), an anti-artrithtis agent, were investigated by cyclic voltammetry and square wave adsorptive stripping voltammetry, respectively. Objective: In this study, we aimed to investigate the electrochemical redox mechanism and develop a nano-sensor for sensitive, fast and selective analysis of meloxicam. Methods: In this study, the three-electrode system was used for all voltammetric measurements. Firstly, the graphene content of GR/CPE sensor was changed in the range of 1.67% to 6.68%. Then, the surface characterization of modified electrode was carried out by using Electrochemical Empedance Spectroscopy and Surface Electron Microscopy methods. Some analytical parameters, such as pH, accumulation potential and accumulation time were optimized and by using optimum parameters, calibration study was established. Results: The GR/CPE with a graphene content of 3.33 % was found to have the best voltammetric signal with a linear working range of 0.1–10 μM. The sensitivity of the quantitative voltammetric method towards M is fairly good with an LOQ of 0.0088 μmol/L and LOD of 0.0026 μmol/L. Conclusion: The optimum pH, accumulation time and accumulation potential were found to be 2.0, 150s and 0.0 V, respectively. The height of the voltammetric signal obtained with the GR/CPE electrode was stable with a 4.0 % deviation for a period of not shorter than 1 months.
Keywords: carbon paste electrode